2016
DOI: 10.1002/jssc.201600980
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an epoxide‐derived metabolite of dictamnine using high‐performance liquid chromatography with hybrid linear trap quadrupole orbitrap mass spectrometry

Abstract: Dictamnine (4-methoxyfuro[2,3-b]quinolone), a furoquinoline alkaloid of the Rutaceae plant family, has been reported to be a phototoxic and photomutagenic compound, whose exposure can cause carcinogenicity, cytotoxicity, and genotoxicity. Metabolic activation is suggested to play an important role in dictamnine-induced toxicities, and the epoxide metabolite of dictamnine has been reported to be the main intermediate in vitro. The objective of this study was to identify N-acetylcysteine conjugate(s) derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…After the oral administration of skimmianine to rats, plasma, urine, and feces samples were collected, extracted, and analyzed as described. The metabolites were predicted by using MetabolitePilot TM software and then confirmed manually based on the above fragmentation pathways of the skimmianine standard and the literature [ 21 , 22 , 23 ]. A total of 16 metabolites were identified in the biological samples originating from rats ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the oral administration of skimmianine to rats, plasma, urine, and feces samples were collected, extracted, and analyzed as described. The metabolites were predicted by using MetabolitePilot TM software and then confirmed manually based on the above fragmentation pathways of the skimmianine standard and the literature [ 21 , 22 , 23 ]. A total of 16 metabolites were identified in the biological samples originating from rats ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Phase II metabolism included glucuronidation and sulfation of some Phase I metabolites. The Phase I metabolic pathways were similar to those of dictamnine, which was also a furoquinoline alkaloid [ 21 , 22 , 23 ]. It seemed that the epoxidation of 2,3-olefinic on the furan ring followed by the hydrolysis of its epoxide ring was a typical characteristic of the furoquinoline alkaloid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…When the benchtop Exactive‐Orbitrap mass spectrometer was launched in 2008 , ultra‐high resolving power (100 000 full‐width at half maximum (FWHM)) has become a power tool for the analysis of different mycotoxins , plant toxins , or alkaloids . However, methods for the determination of TAs based on LC with full‐scan high‐resolution (Orbitrap) MS are scarce, although some of them were applied to determine TAs in food and feed and herbal extracts .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that CYP3A4 was the metabolic enzyme mediating bioactivation of the furan ring in toosendanin and yielded a cis -butene-1,4-dial intermediate ( Yu et al, 2014 ). Considering the molecular structure of DTN possessing a furan ring and was primarily metabolic activated by CYP3A4 ( Feng et al, 2016 ), the present study attempted to define the role of CYP3A4 in DTN-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it was confirmed that DTN was predominantly metabolized into an epoxide intermediate (2,3-epoxide) in vitro , which was primarily in the participation of CYP3A4 ( Wang et al, 2016 ). Furthermore, the epoxide intermediate could subsequently conjugated with N -acetylcysteine to form conjugate with CYP3A4 was primarily responsible for the metabolic activation process ( Feng et al, 2016 ). Thus, evidences have shown the link between the metabolic activation of DTN and CYP3A4, namely CYP3A4 was the predominant enzyme involved in the metabolism of DTN.…”
Section: Introductionmentioning
confidence: 99%